The Effectiveness of Google Classroom Applications on Elementary School Students’ Cognitive Learning Outcomes - Dedi Zulkarnain Pulungan; Jamaris Jamaris; Junifer Siregar (Jurnal Basicedu, 2022)
The purpose of this study was to identify the learning interest of elementary school students following online learning (blended learning) using the google classroom application. This study uses a qualitative method with a descriptive design. The population in this study were fifth grade students in the 2021/2022 academic year. Sampling by purposive sampling is class V which consists of 20 participants from a total population of 48 students. Data collection techniques using triangulation, namely the pretest, posttest, gain, N-gain instruments on cognitive learning outcomes equipped with interview and observation instruments to confirm student learning perceptions. The results showed that the average cognitive learning outcomes of elementary school students pretest was 66.42, posttest results averaged 78.25; the average gain is 11.83 while the N-gain is 0.57 with a percentage increase of 57% which indicates that the use of the application is quite effective in improving the cognitive learning outcomes of elementary school students. While the results of interviews and observations of students and teachers showed a positive response. Students' interest in learning increases with the variants of thematic learning offerings with the Google Classroom application. Meanwhile, the teachers showed a positive attitude that showed an openness to new approaches to learning using digital platforms, especially the Google Classroom learning application.